2020
DOI: 10.1248/yakushi.20-00167
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Epalrestat against Oxidative Stress-induced Cytotoxicity

Abstract: Epalrestat (EPS), approved in Japan, is currently the only aldose reductase inhibitor that is available for the treatment of diabetic neuropathy. Recently, we found that EPS at near-plasma concentration increases the intracellular levels of glutathione (GSH) in rat Schwann cells. GSH, the most abundant non-protein thiol antioxidant in cells, is important for protection against oxidative stress. Oxidative stress is associated with the development and progression of many pathological conditions, such as atherosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
1
0
1
Order By: Relevance
“…Our current study has demonstrated findings supporting the ability of CMTI to restore thiol‐disulfide homeostasis 48 . Similarly, STB inhibits GSH oxidation in diabetic tissues 49 and EPA protects GSH levels rat Schwann cells 50 …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our current study has demonstrated findings supporting the ability of CMTI to restore thiol‐disulfide homeostasis 48 . Similarly, STB inhibits GSH oxidation in diabetic tissues 49 and EPA protects GSH levels rat Schwann cells 50 …”
Section: Discussionsupporting
confidence: 76%
“…48 Similarly, STB inhibits GSH oxidation in diabetic tissues 49 and EPA protects GSH levels rat Schwann cells. 50 In this study, GST was inhibited in diabetic retina and activated in diabetic lens. In addition, CMTI treatment reduced GST activity below control values in both lens and retina of F rats.…”
Section: Discussionmentioning
confidence: 60%
“…化を介して,g-glutamate-cysteine ligase(GCL)の 発現量を増加させることを明らかにしてきた. 5,9) GCL は GSH 生 合成の 律速 酵素で あり ,EPS は 32,34,35) 細胞内への Cd の取り込みは亜鉛トラン スポーターが関与し,そのなかでも細胞外や細胞内 小器官から細胞質に亜鉛を輸送する Zrt-, Irt-like protein (ZIP)が関与していることが明らかにされ ている. 32,35,38) Cd 毒性に対して高い感受性を示すマ ウスの系統では,血管内皮細胞の ZIP8 が高発現し ていることが報告されている. 39) 血管内皮細胞を Cd で曝 露する と, ZIP8 の発 現が 強く誘 導さ れ…”
unclassified